Determinants of the decision to adopt integrated soil fertility management practices by smallholder farmers in the central highlands of Kenya - Mugwe, J; Mugendi, DN; Mucheru-Muna, M.; Merckx, Roel; Chianu, Jonas N.; Vanlauwe, Bernard (Cambridge University Press, 2009)
Declining soil fertility is a major cause of low per capita food production on smallholder farms of sub-Saharan Africa. This study attempted to provide an empirical explanation of the factors associated with farmers’ decisions to adopt or not to adopt newly introduced integrated soil fertility management (ISFM) technologies consisting of combinations of organics and mineral fertilizer in Meru South district of the central highlands of Kenya. Out of 106 households interviewed, 46% were ‘adopters’ while 54% were ‘non-adopters’. A logistic regression model showed that the factors that significantly influenced adoption positively were farm management, ability to hire labour and months in a year households bought food for their families, while age of household head and number of mature cattle negatively influenced adoption. The implication of these results is that the adoption of ISFM practices could be enhanced through targeting of younger families where both spouses work on the farm full-time and food insecure households. It is also important to target farmers that lack access to other sources of soil fertility improvement. Examples include farmers that do not own cattle or those owning few and who, therefore, have limited access to animal manure.